A guide for banding North Island robin (Petroica longipes) nestlings. Issue 3 (2nd July 2016) - Parker, KA; Lovegrove, TG; Chambers, R; Harmer, A
ABSTRACT: Measures of population productivity and individual survival are essential for effective conservation management and scientific investigations. In studies of birds, individuals are often marked with unique colour band combinations to enable estimates of population vital rates. If birds are banded in the nest this must be done at the correct stage in nestling development. If nestlings are banded too early it can lead to leg damage. If they are banded too late it can cause early fledging and reduced survival. Here, we use photographs to guide estimation of the best stage to band North Island robin ( Petroica longipes ), or toutouwai, nestlings, which is typically at 9–12 days of age.